WP1066 suppresses macrophage cell death induced by inflammasome agonists independently of its inhibitory effect on STAT3 - Honda, Shino (Cancer Sci, 2017)
The compound WP1066 was originally synthesized by modifying the structure of AG490, which inhibits the activation of signal transducer and activator of transcription 3 (STAT3) by directly targeting Janus kinases (JAKs). WP1066 exhibits stronger anti‐cancer activity than AG490 against malignant glioma and other cancer cells and is regarded as a promising therapeutic agent. By screening a small library of target‐known compounds, we identified WP1066 as an inhibitor of macrophage cell death induced by agonists of the NLRP3 inflammasome, an intracellular protein complex required for the processing of the proinflammatory cytokine interleukin (IL)‐1β. WP1066 strongly inhibited cell death as well as extracellular release of IL‐1β induced by inflammasome agonists in mouse peritoneal exudate cells and human leukemia monocytic THP‐1 cells that were differentiated into macrophagic cells by treatment with PMA. However, inflammasome agonists did not increase STAT3 phosphorylation, and another JAK inhibitor, ruxolitinib, did not inhibit cell death, although it strongly inhibited basal STAT3 phosphorylation. Thus, WP1066 appears to suppress macrophage cell death independently of its inhibitory effect on STAT3. In contrast, WP1066 itself induced the death of undifferentiated THP‐1 cells, suggesting that WP1066 differentially modulates cell death in a context‐dependent manner. Consistent with previous findings, WP1066 induced the death of human glioma A172 and T98G cells. However, neither ruxolitinib nor AG490, the former of which completely suppressed STAT3 phosphorylation, induced the death of these glioma cells. These results suggest that WP1066 targets cell death‐modulating molecules other than those involved in JAK‐STAT3 signaling.